Caterina Depicted - Hadjikyriakos, Iosif (Actual Problems of Theory and History of Art, 2019)
One of the emblematic figures in the relationship between the Venetian Republic and the East is, without doubt, Caterina Cornaro, wife of the King of Cyprus, Jerusalem and Armenia, subsequently herself queen of the island, but, most importantly, ‘daughter’ of Venice. There are not many paintings depicting Caterina, produced either in her lifetime (1454–1510) or later. In all the works produced during her life, Caterina is depicted as a secular, royal figure, dressed in the Venetian manner of the time. In the works produced from the second half of the 16th century onwards, the Queen of Cyprus is depicted more freely, without any of the social stereotypes relating to her status. During the 1540s, Titian paints Caterina Cornaro as Saint Catherine of Alexandria. The artist’s well known painting, now in Florence, for the first time depicts the Queen wearing a rich, short-sleeved cloak. This garment, in many variations, was meant to mark a long series of paintings depicting Caterina Cornaro as well as other women of the East for the next century. But why does the Venetian artist choose to dress the Queen of Cyprus in this garment? Did Caterina Cornaro ever wear clothes of an Eastern type? How did other women of the East dress during that period? Drawing on the context laid out above, as well as the study of contemporary sources, I try to answer these questions bearing in mind the political and financial relationships between a dying Empire and one close to its peak. The works of Titian and his followers are critically compared to the portraits of Caterina Cornaro made during her lifetime, especially in the attire. At the same time, the cloak shown in Titian’s painting is compared to pictorial and other sources from the Ottoman world, in an effort to trace the Venetian artist’s inspiration.
Keywords: Venice; Cyprus; Ottoman; costumes; Caterina Cornaro; Sayia; fashion; Oriental attire; Titian